Vegetative disorders in anxiety disorder: A review - Vladislav Y. Marchenko; Dmitry S. Petelin (Consilium Medicum, 2023)
Vegetative disorders are characteristic of patients with anxiety disorders, which are becoming more common and negatively affect the quality of life of both the patients themselves and their environment. Almost 20% of the population suffers from anxiety disorders, and women are more prone to these diseases than men. Anxiety disorders include panic disorder, generalized anxiety disorder, and other disorders. In most cases, anxiety disorders are accompanied by vegetative symptoms, such as palpitations, sweating, trembling, changes in appetite and others. Vegetative disorders often mimic somatic and neurological disorders in patients with anxiety disorders, therefore they create problems for diagnosis. In our country, a significant part of patients with anxiety disorders are observed by neurologists with a diagnosis of somatoform dysfunction of the autonomic nervous system or autonomic dystonia. The therapy of the underlying disease, which includes lifestyle optimization, psychotherapy and medications, is of leading importance in reducing vegetative disorders.